INTEGRATION OF SELF-ESTEEM ENHANCEMENT PROGRAMS IN COLLEGE OUTREACH ACTIVITIES TO PERSONS WITH DISABILITIES: TOWARD A FRAMEWORK FOR INCLUSIVE PEDAGOGY - Rosalyn Laylo Ward; Rafael Ibe Santos (Sanata Dharma University Yogyakarta, 2026)
This study explores the development of self-esteem among individuals with physical conditions through proposed self-esteem enhancement programs by faculty and students engaged in outreach activities at a local private college in Rizal province for persons with disabilities (PWDs), who are often excluded from mainstream education. Relying on autoethnography as a research method, this qualitative work provides timely observations and reflections drawn from recorded research notes on the subject of self-esteem as it relates to individuals with physical challenges and what can be done to address their needs outside the four walls of educational institutions. Major autoethnographic findings highlight some of the best possible practices necessary in the conduct of self-esteem enhancement tasks for PWDs and how they can be implemented in places such as Tahanang Walang Hagdanan (Home Without Stairs), a pioneering organization that empowers persons with disabilities by providing livelihood, skills training, and advocacy for accessibility and inclusion in the Philippines. Our autoethnographic records further point to the need to identify self-esteem enhancement strategies that can be integrated into the faculty-student community outreach endeavors designed for people with physical limitations. Observations and conclusions have implications for inclusive pedagogy and a framework for education that integrates those with disabilities in formal and non-formal education in line with the United Nations Sustainable Development Goals (SDGs) in Education, particularly SDGs 4.3 and 4.5.